2000
DOI: 10.1038/35005101
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-MAPK pathway is important for olfaction in Caenorhabditis elegans

Abstract: The Ras-MAPK (mitogen-activated protein kinase) signal transduction pathway is well known to control cellular proliferation and differentiation in response to extracellular signals, but its other functions are less understood. In Caenorhabditis elegans this pathway regulates several developmental events, such as vulval induction and progression of meiosis, but its function in the nervous system is unknown. Here we report that the Ras-MAPK pathway is involved in olfaction in this organism. Mutational inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 29 publications
3
77
1
Order By: Relevance
“…Interestingly, genetic mutation of the Ras homologue LET-60 Ras disrupts chemotaxis in Caenorhabditis elegans, suggesting that ERK/MAP kinase may contribute to olfactory detection in simpler organisms (50). In contrast to our study with mice that demonstrated odorant stimulation of ERK/MAP kinase maximally at 5 min, odorant stimulation of ERK/MAP kinase in C. elegans occurs within seconds.…”
Section: Discussioncontrasting
confidence: 80%
“…Interestingly, genetic mutation of the Ras homologue LET-60 Ras disrupts chemotaxis in Caenorhabditis elegans, suggesting that ERK/MAP kinase may contribute to olfactory detection in simpler organisms (50). In contrast to our study with mice that demonstrated odorant stimulation of ERK/MAP kinase maximally at 5 min, odorant stimulation of ERK/MAP kinase in C. elegans occurs within seconds.…”
Section: Discussioncontrasting
confidence: 80%
“…The let-60 gene acts genetically downstream of let-23 with respect to vulva development and upstream of the MAPK pathway with respect to chemotaxis [46], [47]. The rab-1 , rab-6.2 , rab-28 and rab-37 have all been shown in other model systems to regulate intracellular membrane trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…2e include tax-4 cDNA that was PCR amplified from pDEST- tax-4cDNA (a gift from Dr Iino)35 and the 3′-untranslated region of unc-54 . In addition, pTOM4 includes the ASJ-specific trx-1 promoter (1.0 kb)36, which was from pQZ37 trx-1p::ICE (a gift from Dr Alcedo).…”
Section: Methodsmentioning
confidence: 99%